Некоторые аспекты повышения эффективности защиты низковольтного электрооборудования - Терешин, В. Н.; Богданова, Л. Е. (Національний технічний університет "Харківський політехнічний інститут", 2004)
Рассмотрены некоторые пути снижения площади разброса защитных характеристик автоматических выключателей за счет: материала и конструкции теплового расцепителя; способа калибровки; конструктивного исполнения механизма свободного расцепления.

Some ways of circuit breakers improving by decreasing variation of their protective characteristics are considered with an account of materials property, constructions of thermal trip and mechanism of free unlinking and method of their calibration.
Some aspects of protection efficiency rising in the low-voltage electrical equipment
Keywords: автоматический выключатель; низковольтное электрооборудование; механическая память формы; механизм свободного расцепления; деформация; low-voltage electrical equipment; circuit breaker; protective characteristics; thermal trip